Experimental Analysis of an External Dynamic Solar Shading Integrating PCMs: First Results. (November 2015) - Komerska, Anna; Bianco, Lorenza; Serra, Valentina; Fantucci, Stefano; Rosiński, Marian
Abstract: This paper presents the first results of an experimental analysis on dynamic translucent solar shadings with PCM, aimed at demonstrating its potential on reducing internal solar heat gains. The study is focused on the assessment of the thermal performance of the prototype panel during the solid phase of the PCM through an experimental campaign in a test cell facility. The total daily solar heat gains were reduced by more than 50% compared to the non-shaded reference triple glazing unit and the internal surface temperature of the glazing decreased of more than 6 °C during the maximum external incident solar radiation.